Consolidation Behavior and Compression Prediction Model of Coastal Cement Soil Modified by Nanoclay - Wenjie Yu; Na Li; Mengdan Dai; Dongliang An; Biao Qian; Wei Wang; Ping Jiang (Advances in Materials Science and Engineering)
Coastal cement soil modified by nanoclay (NCS) has particular research significance as a modification approach to improve the high compressibility of coastal cement soil (CCS). At curing ages of 7 days and 28 days, consolidation and SEM tests were performed on 6 groups of NCS samples with a nanoclay content between 0% and 10% and 6 groups of CCS samples with a cement content between 10 and 20%, and a compression prediction model was established based on the test results. Test results show that (1) there is a linear interval for the improvement effect of the increment of cement content on the compression of CCS samples. In this test, the cement content in this interval is between 12% and 18%. CCS with a cement content of 18% is preferred. (2) The improvement effect on the compression of the sample is better with a nanoclay content of 4% and 8%, but poor with a content of 2%. At a consolidation pressure between 100 kPa and 800 kPa, NCS with a nanoclay content of 4% is preferred. (3) Adhesion is better with a nanoclay content of 4%, and the filling effect is better with a content of 8%. (4) The cosine-power function-exponential model is established, and the measured data are fitted, and a prediction model for the compression amount of CCS and NCS is established.